2021
DOI: 10.21608/ejhc.2021.142233
|View full text |Cite
|
Sign up to set email alerts
|

Health Awareness Package to Avert Helicobacter Pylori Infection among Family Members

Abstract: Helicobacter pylori are common bacteria that cause pain and may lead to ulcers or stomach cancer. The awareness package is a process that educates family members to promote their knowledge and practice towards the prevention of infection. Aim: Evaluate the effect of a health awareness package to avert helicobacter pylori infection among family members. Design: A quasi-experimental design was utilized. Setting: The study was carried out in the internal medicine outpatient clinic at Helwan General Hospital. Samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
3
0
0
Order By: Relevance
“…The current study also showed that 55% of the studied children were male. The results of this research agreed with those of Deng et al [24] , who investigated the antibiotic resistance of H. pylori strains obtained from Southwest China pediatric patients and found that patients who were found to be H. pylori positive (53%) were boys. This current study reported that majority of children had no previous hospitalization related to H. pylori infection.…”
Section: Discussionsupporting
confidence: 91%
“…The current study also showed that 55% of the studied children were male. The results of this research agreed with those of Deng et al [24] , who investigated the antibiotic resistance of H. pylori strains obtained from Southwest China pediatric patients and found that patients who were found to be H. pylori positive (53%) were boys. This current study reported that majority of children had no previous hospitalization related to H. pylori infection.…”
Section: Discussionsupporting
confidence: 91%
“…13 Interestingly, the study showed low awareness among both health and non-health science university students, indicating the need for educational programs to enhance students' awareness of H. pylori infection, which is a public health concern. Our finding of a significant increase in overall and domain-wise knowledge of H. pylori infection after the educational intervention is comparable to the findings of Ibrahiem and Saad (2021), who evaluated a health awareness package for H. pylori among family members in a hospital in terms of knowledge and hygienic practices in Egypt. 16 Although their findings are comparable to our study's, there are some differences.…”
Section: Discussionsupporting
confidence: 86%
“…Our finding of a significant increase in overall and domain-wise knowledge of H. pylori infection after the educational intervention is comparable to the findings of Ibrahiem and Saad (2021), who evaluated a health awareness package for H. pylori among family members in a hospital in terms of knowledge and hygienic practices in Egypt. 16 Although their findings are comparable to our study's, there are some differences. For instance, their sample involved family members, and they used face-to-face small-group education with a booklet.…”
Section: Discussionsupporting
confidence: 86%